EFFECTS OF DRYING METHODS ON THE NUTRITIONAL, ANTINUTRITIONAL, AND ANTIOXIDANT PROPERTIES OF PINEAPPLE (Ananas comosus) INDUSTRY WASTE AS A POTENTIAL FEED ADDITIVE - JHON WARY E. REPAMONTE; FIONA L. PEDROSO; FERNIE A. CATIENZA; CASIANO H. CHORESCA JR.; FERNAND F. FAGUTAO; GWEN ANUEVO; MARY JANE S. APINES-AMAR; MARK LLOYD BAJALLA (Journal of Animal and Plant Sciences, 2025)
A major challenge for many countries is managing agricultural waste. For instance, the pineapple processing industry in the Philippines generates tons of waste each year. Thus, this study aims to assess the impact of different drying methods (sun drying, oven drying, and dehydration) on the proximate composition, antinutritional, and antioxidant properties of pineapple industry waste, to determine its suitability for various applications. The results showed that sun-dried pineapple waste had a higher carbohydrate content compared to other treatments. Dehydrated pineapple samples had higher percentages of fiber (43.60 ± 0.43), ash (2.93 ± 0.03), protein (5.48 ± 0.08), and fat (1.00 ± 0.11) compared to sun-dried samples. Dehydrated pineapple industry waste had significantly higher tannin content mg TAE/100g (0.1388±0.00) compared to oven-dried (0.1009±0.00) and sun-dried (0.0877±0.00), while oven-dried samples had the highest phytate content (0.077±0.03), followed by dehydrating and sun drying. Non-significant differences in antioxidant activities (DPPH scavenging activity) and total phenolic content (TPC) were noted among the drying treatments. Oven-dried samples had a higher total flavonoid content (TFC) compared to dehydrated samples; however, the difference was not statistically significant when compared to sun-dried samples. This study suggests that sun drying and dehydration, due to their lower energy consumption and ability to maintain product nutrition, are viable options for mass-producing pineapple industry waste for other applications such as feed additive. Preserving the nutritional integrity of the waste could offer significant advantages for its utilization in the Philippine pineapple industry.
Keywords: Pineapple; Antioxidants; Proximate composition; Drying process; Antinutritional; Aquafeeds